Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1038/leu.2010.233
|View full text |Cite
|
Sign up to set email alerts
|

Chemoproteomics-based kinome profiling and target deconvolution of clinical multi-kinase inhibitors in primary chronic lymphocytic leukemia cells

Abstract: The pharmacological induction of apoptosis in neoplastic B cells presents a promising therapeutic avenue for the treatment of chronic lymphocytic leukemia (CLL). We profiled a panel of clinical multi-kinase inhibitors for their ability to induce apoptosis in primary CLL cells. Whereas inhibitors targeting a large number of receptor and intracellular tyrosine kinases including c-KIT, FLT3, BTK and SYK were comparatively inactive, the CDK inhibitors BMS-387032 and flavopiridol showed marked efficacy similar to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 49 publications
0
68
0
Order By: Relevance
“…However, dasatinib inhibits Src kinase activation in CLLcellsandelicitsasubstantialportionofsample-specific biologicalresponseat100-foldlowerconcentrationsthanare requiredforefficientapoptosisinductionbysorafenib.When testedataconcentrationof1mM,dasatinibandsorafenibinduced little if any apoptosis in CLL samples and were both ratedasweakinducersofapoptosisascomparedtothecyclindependent kinase (CDK) inhibitors BMS-387032 and flavopiridol [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, dasatinib inhibits Src kinase activation in CLLcellsandelicitsasubstantialportionofsample-specific biologicalresponseat100-foldlowerconcentrationsthanare requiredforefficientapoptosisinductionbysorafenib.When testedataconcentrationof1mM,dasatinibandsorafenibinduced little if any apoptosis in CLL samples and were both ratedasweakinducersofapoptosisascomparedtothecyclindependent kinase (CDK) inhibitors BMS-387032 and flavopiridol [26].…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with CML were generated by Bcr-Abl, a fusion gene formed by a reciprocal chromosomal translocation t(9;22)(q34;q11) (39)(40)(41). Both patients with HES with FIP1L1-PDGFRa addiction and patients with CML generally respond to imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…Kinobeads were originally developed for selectivity profiling of small molecule kinase inhibitors (22), but we and others have also shown that kinobeads can be employed to identify kinases from human tissue including tumor cells isolated from patients (25). However, direct proteomic analysis of patient samples, although desirable, is challenging because of the often limited available sample quantity, varying ratios of tumor versus stroma versus vasculature, extent of necrosis and hypoxia, infiltration of inflammatory cells, etc., as well as significant issues with candidate validation options.…”
Section: Evaluation Of C-met As a Target In Hnscc-it Has Been Suggestmentioning
confidence: 99%
“…The second element is intensitybased label-free quantitative mass spectrometry that enables the identification and relative quantification of the purified proteins across many biological samples (24). Although the Kinobeads approach was initially developed to profile the selectivity of small molecule kinase inhibitors, it also lends itself to profiling the expression of kinases in cells or tissues (22,25). In this study, we utilized the Kinobeads approach to identify systematically kinases from HNSCC cell lines that might represent novel candidate targets for individualized therapeutic intervention and/or candidate biomarkers.…”
mentioning
confidence: 99%